Estimation of wastewater use at the Teófilo Otoni sewage treatment plant, Minas Gerais, in pasture fertigation (Research, Society and Development, 2020)
Wastewater is a source of organic matter and mineral nutrients for the soil and plants, also contributing to the supply of water via fertigation. The present study aimed to evaluate the potential of treated wastewater at the sewage treatment plant in the city of Teófilo Otoni and its use in pasture fertigation. The chemical data of the wastewater were collected at COPASA by Teófilo Otoni and the calculations based on the dystrophic characteristics of the region's soils. The potential for use, quantification and the capacity to serve local grazing areas were evaluated. The results showed that the wastewater treated at the Teófilo Otoni sewage treatment plant has excellent chemical characteristics with a slightly basic pH (7.45) and a high concentration of nitrogen (50.07 mg.L-1) and phosphorus (6.13 mg.L-1). Another important point is associated with the high amount of residual water generated, values that reach almost 100 liters per second. Considering the reduced fertility of pasture soils in the region, the use of wastewater from the sewage treatment plant on a continuous basis would meet the total phosphorus needs and partially meet the nitrogen needs of two to four hectares per day. Considering that the residual water and the nutrients contained are discarded in the All Saints river with high risks of eutrophication, the use of water in fertigation, in addition to the financial benefits to the rural producer, would also bring environmental benefits to the water resources.